Identification of aerodynamic coefficients of a projectile and reconstruction of its trajectory from partial flight data - Condaminet, Vincent; Delvare, Franck; Choï, Daniel; Demailly, Hélène; Grignon, Christophe; Heddadj, Settie (Computer Assisted Methods in Engineering and Science, 2017)
Several optimization techniques are proposed both to identify the aerodynamic coefficients and to reconstruct the trajectory of a fin-stabilized projectile from partial flight data. A reduced ballistic model is used instead of a more general six degree of freedom (6DOF) ballistic model to represent the flight of the projectile. Optimization techniques are proposed in order to identify the set of aerodynamic coefficients. These techniques are compared when identifying the aerodynamic coefficients from both exact and noisy simulated partial flight data.